Oxford Spanish wordpack (Oxford University Press, 2000)
This "Wordpack" provides a thematic grouping of essential vocabulary from key language areas: people, house, city and world. These are then broken down and arranged in topics - for example, parts of the body, family and friends - forming an easy-access, quick-reference vocabulary finder and builder. The book both supports the "Oxford Take Off in Spanish" and "Oxford Take Off in Latin American" Spanish language learning packages, and is a stand-alone product for users at all levels